2002
DOI: 10.1037/0278-6133.21.2.139
|View full text |Cite
|
Sign up to set email alerts
|

The DRD4 VNTR polymorphism moderates craving after alcohol consumption.

Abstract: Recent research has suggested that alterations in mesolimbic dopamine neurotransmission are central to the development and expression of craving for alcohol. Because the D4 dopamine receptor gene, variable numbers of tandem repeats (DRD4 VNTR) polymorphism putatively expresses functional differences in dopamine receptors, the present study tested whether this polymorphism influences the effects of a priming dose of alcohol on craving. Participants consumed 3 alcoholic drinks or 3 control drinks and completed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
142
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 57 publications
14
142
0
5
Order By: Relevance
“…In addition, future work with the DRD4 VNTR will determine how consistent this effect is across studies on alcohol craving and, more generally, studies of appetitive motivation. To date, studies have suggested that the DRD4 VNTR may influence appetitive motivation for alcohol (Hutchison et al, 2002a), tobacco (Hutchison et al, 2002b), and food (Sobik et al, under review).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, future work with the DRD4 VNTR will determine how consistent this effect is across studies on alcohol craving and, more generally, studies of appetitive motivation. To date, studies have suggested that the DRD4 VNTR may influence appetitive motivation for alcohol (Hutchison et al, 2002a), tobacco (Hutchison et al, 2002b), and food (Sobik et al, under review).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic Analyses: DNA Collection, Extraction, and Storage DNA from cheek swabs was collected and extracted following published procedures (see Freeman et al, 1997;Hutchison, McGeary, Smolen, Bryan, & Swift, 2002;Walker et al, 1999). The BDNF SNP was assayed using a commercially available 5′-nuclease (TaqMan, Roche Molecular Systems, Pleasanton, CA) assay in conjunction with the 7500 thermocycler (Applied Biosystems, Foster City, CA; see Livak, 1999, for description of the TaqMan assay).…”
Section: Rating Of Perceived Exertion (Rpe)-mentioning
confidence: 99%
“…Functional neuroimaging of recently detoxified alcoholics suggests that participants who carry the 7 or more repeats in the DRD4 VNTR (DRD4L) show increased activation to alcohol-related stimuli in the anterior cingulate and associated prefrontal cortical areas compared with participants who carry only shorter variants (DRD4S) (Smolka, McGeary, et al, 2005, manuscript under review). Laboratory studies of reactivity to associated cues have shown greater subjective urges reported by DRD4L participants compared to DRD4S participants in smoking and alcohol studies (Hutchison, Lachance et al, 2002;Hutchison, McGeary et al, 2002;McGeary et al, 2001), a study of heroin addicts (Shao et al, 2006), and even a study related to food craving (Sobik et al, 2005). Pharmacogenetic studies suggest the differential subjective urge for alcohol may be attenuated by a D4 receptor antagonist relative to active placebo (Hutchison et al, 2003).…”
Section: Introductionmentioning
confidence: 99%